Integrated water availability modelling to assess sustainable agricultural intensification options in the Meki Catchment, Central Rift Valley, Ethiopia - Taye, Meron Teferi; Ebrahim, Girma Yimer; Nigussie, Likimyelesh; Hagos, Fitsum; Uhlenbrook, Stefan; Schmitter, Petra S. (Informa UK Limited, 2022)
The Meki catchment in the Central Rift Valley basin of Ethiopia is currently experiencing irrigation expansion and water scarcity challenges. The objective of this study is to understand the basin’s current and future water availability for agricultural intensification. This was done by simulating scenarios through an integrated SWAT-MODFLOW model to assess the water balance. The scenarios were co-developed with communities who expressed their aspirations for agricultural intensification in conjunction with projected climate change. The results show that with the present land use and climate, the catchment is already water stressed and communities cannot meet their irrigation water demand, particularly in the first irrigation season (October–January). However, in the second irrigation season (February–May) water resource availability is better and increasing irrigated area by 50% from the present extent is possible. With a climate change scenario that favours more rainfall and shallow groundwater use, agricultural intensification is feasible to some extent.